Children’s Position from Interfaith Matrimony Following the Issuance of the Supreme Court Circular No. 2 of 2023 - nisa, ardina khairun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Matrimony, in Islamic law, has a close and inseparable relationship with religion. In fact, almost all religions regulate the issue of matrimony between a man and a woman of the same religion as the most important and highly crucial basis for determining the success of a person’s domestic life because of the birth of a child. The reasons for a child’s position and status are determined based on whether or not their parents’ matrimony is valid. Matrimony between different religions causes problems related to parenting patterns until the children grow up and get married, receiving inheritance and so on. This research aims to find out what the position of children from interfaith matrimony was before and the position after the issuance of Supreme Court Circular No. 2 of 2023. This research used a statutory approach with the normative legal method, and the data analysis method used is qualitative juridical. The results revealed that the position of the child before the issuance of the Supreme Court Circular No. 2 of 2023 is valid and recorded because the parents granted the matrimony petition through the court and the position of the child following the issuance of the Supreme Court Circular No. 2 of 2023 is invalid and is not recorded because it is prohibition on accepting inter-religious matrimony, but special regulations are still needed to determine the position and children resulting from inter-religious matrimony